2022
DOI: 10.1093/rheumatology/keac218
|View full text |Cite
|
Sign up to set email alerts
|

Survival analysis of mortality and development of lupus nephritis in patients with systemic lupus erythematosus up to 40 years of follow-up

Abstract: Objectives Patients with systemic lupus erythematosus (SLE) have increased mortality compared with age and sex-matched controls. Lupus nephritis (LN) is a severe manifestation of SLE and an important cause of death. We carried out a retrospective survival analysis to investigate factors that could influence risk of mortality and LN in a large multi-ethnic cohort of patients with SLE. Methods By careful review of medical recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
1
4
0
1
Order By: Relevance
“…Patients with renal involvement were younger than patients with non-renal SLE in our cohort. In agreement with previous reports [15], we also found younger age of SLE onset in LN patients than in those without kidney involvement. In opposition to most previous studies [16], there was no significant difference between men in women in LN and non-renal SLE groups.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…Patients with renal involvement were younger than patients with non-renal SLE in our cohort. In agreement with previous reports [15], we also found younger age of SLE onset in LN patients than in those without kidney involvement. In opposition to most previous studies [16], there was no significant difference between men in women in LN and non-renal SLE groups.…”
supporting
confidence: 93%
“…Besides, a higher proportion of LN patients had necrotizing vasculitis (9.2% vs 2.0%) and a history of arterial/venous thrombosis (9.7% vs 2.5%) compared to patients without kidney involvement. In addition, the SLEDAI score of LN patients was significantly higher (14 (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) points vs 8 (4-14) points, p<0.001) than in non-renal SLE patients. The frequency of anemia, leukopenia, and thrombocytopenia did not differ significantly between the groups.…”
mentioning
confidence: 87%
“…In a prospective study on the long-term survival of newly diagnosed SLE patients in China [42], it was found that in the early univariate analysis, age growth was a predictor of mortality, but in the late multivariate model, it was found that age was replaced, and organ damage in the early stage of the disease was more important, which meant that the increase in mortality in patients with delayed SLE was more related to early organ damage than age itself [43]. Biogenetic analysis found that lupus nephritis in Asian patients had higher levels of autoantibodies, higher frequency of lupus nephritis and higher prevalence of active glomerulonephritis compared with white patients [44]. At the same time, it was found that the incidence of lupus nephritis in Asian patients was younger (the most common damage in children with SLE was kidney, neuropsychiatric system, optic nerve system and skeletal muscle [45]), system involvement was faster, organ damage was earlier, and neuropsychiatric damage score was more serious at 5 years.…”
Section: Comparison Of Genotype and Allele Frequencies Of Vegf Gene R...mentioning
confidence: 99%
“…Trotz erheblicher Verbesserungen in der Therapie, die zu einer besseren Kontrolle der Krankheit geführt haben, sind Patient*innen mit LN nach wie vor einem hohen Mortalitätsrisiko ausgesetzt, das insbesondere durch kardiovaskuläre und infektiöse Komplikationen sowie durch Malignome bedingt ist [ 60 62 ]. Die Prävention von Organschäden und eine angemessene Behandlung von Komorbiditäten sind unerlässlich, um die durch die Krankheit und immunsuppressive Therapie bedingte Mortalität in dieser Patientengruppe zu minimieren.…”
Section: Behandlung Von Nicht-proliferativen Formen Der Lnunclassified